Meaning and context in the thanksgiving hymns: linguistic and rhetorical perspectives on a collection of prayers from Qumran - Hasselbalch, Trine (Early Judaism and its literature, 2015)
"This book challenges the consensus that the Hodayot consist of leader hymns and community hymns respectively, and it breaks with the habit of interpreting each hymn as expressing basically either leadership issues or ordinary community member issues. Instead it argues that all of the compositions in 1QHodayota were perceived by their owners to express the sentiments of a worshipping community at large, and that the members of this community saw themselves as holding a mediating position in the agency of God. This way, the Hodayot express a theology according to which God acts in the world through the members of this particular community, and the collection of 1QHodayota seems to reflect an emergent socio-religious pattern which is different from that of the Book of Psalms. The book engages in an array of methods, most prominently from the field of sociolinguistics, in an attempt to find more sophisticated ways to approach the relationship between the Dead Sea scrolls, in this case the Hodayot, and their socio-historical contexts"--